Higher antibody titres against Pseudogymnoascus destructans are associated with less white-nose syndrome skin lesions in Palearctic bats - Pikula, Jiri; Brichta, Jiri; Seidlova, Veronika; Piacek, Vladimir; Zukal, Jan (Frontiers in Immunology, 2023)
Serological tests can be used to test whether an animal has been exposed to an infectious agent, and whether its immune system has recognised and produced antibodies against it. Paired samples taken several weeks apart then document an ongoing infection and/or seroconversion. In the absence of a commercial kit, we developed an indirect enzyme-linked immunosorbent assay (ELISA) to detect the fungus-specific antibodies for Pseudogymnoascus destructans, the agent of white-nose syndrome in bats. Samples collected from European Myotis myotis (n=35) and Asian Myotis dasycneme (n=11) in their hibernacula at the end of the hibernation period displayed 100% seroprevalence of antibodies against P. destructans, demonstrating a high rate of exposure. Our results showed that the higher the titre of antibodies against P. destructans, the lower the infection intensity, suggesting that a degree of protection is provided by this arm of adaptive immunity in Palearctic bats. Moreover, P. destructans infection appears to be a seasonally self-limiting disease of Palearctic bats showing seroconversion as the WNS skin lesions heal in the early post-hibernation period.